2021
DOI: 10.3390/v13091731
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Extraction and Detection of African Swine Fever Virus DNA Based on Isothermal Recombinase Polymerase Amplification Assay

Abstract: African swine fever virus (ASFV) is the causative agent of a deadly disease in pigs and is spread rapidly across borders. Samples collected from suspected cases must be sent to the reference laboratory for diagnosis using polymerase chain reaction (PCR). In this study, we aimed to develop a simple DNA isolation step and real-time recombinase polymerase amplification (RPA) assay for rapid detection of ASFV. RPA assay based on the p72 encoding B646L gene of ASFV was established. The assays limit of detection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
(53 reference statements)
0
20
0
Order By: Relevance
“…Another concern for the implementation of these techniques in the field relates to the need for DNA extraction, which also requires equipment that is not readily available in the field (Inui et al, 2022). In this regard, previous studies have shown that pathogen lysis through heating, can be used for nucleic acid release without the need for extraction columns or laboratory equipment (Ceruti et al, 2021;Yang et al, 2022). However, these studies have been performed using reagents, such as lysis buffers and pH stabilizers, that are not readily available at the point of care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another concern for the implementation of these techniques in the field relates to the need for DNA extraction, which also requires equipment that is not readily available in the field (Inui et al, 2022). In this regard, previous studies have shown that pathogen lysis through heating, can be used for nucleic acid release without the need for extraction columns or laboratory equipment (Ceruti et al, 2021;Yang et al, 2022). However, these studies have been performed using reagents, such as lysis buffers and pH stabilizers, that are not readily available at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…Ten samples from each of the four matrices were diluted in water at a 1:10 proportion and afterwards were spiked with pSLA DNA at a concentration of 5*10 2 plasmid copies/uL. Additionally, to simulate a nucleic acid extraction method to be easily performed in field conditions, the samples were boiled at 100°C for 15 minutes (Ceruti et al, 2021;Yang et al, 2022). Afterwards, nonspiked and spiked samples were evaluated by fluorometric and colorimetric LAMP detection.…”
Section: Lamp Testing Of Dna-spiked Samplesmentioning
confidence: 99%
“…Another potential decentralized testing strategy is to pair the HCV RT-RPA assay with a simple benchtop sample preparation method to create a stream-lined diagnostic protocol that can be performed in low-complexity laboratories in clinical settings by nurses or other technical staff. Several studies have demonstrated the feasibility for similar field-deployable RT-RPA assays using a laboratory-in-a-suitcase and simple user protocol for viral detection [54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…: MN393476.1) using the software Oligo 7 (Molecular Biology Insights, Inc., USA). The p72 gene was selected as a target gene because of its high specificity to ASFV [ 7 8 11 16 19 21 22 ]. The length of the selected target was 118 nt, and its GC content was 48.3%.…”
Section: Methodsmentioning
confidence: 99%
“…The assays based on immunology include colloidal gold test strip assay [ 4 ], time-resolved fluorescence immunoassay [ 5 ], fluorescent immunochromatography test strip [ 6 ], amplified luminescent proximity homogeneous assay (AlphaLISA) [ 7 ], triplex bead-based assay for the simultaneous detection of antibodies [ 8 ], Eu (III) chelate microparticle-based lateral flow test strip and blocking enzyme-linked immunosorbent assay [ 2 9 ]. Many nucleic acid amplification methods have been improved or modified for the detection of ASFV, such as multiplex reverse transcription-polymerase chain reaction (RT-PCR) assay [ 10 ], triplex real-time PCR assay [ 11 ], real-time loop-mediated isothermal amplification (LAMP) assay [ 12 13 ], LAMP combined with lateral flow dipstick [ 14 ], semi-quantitative colorimetric LAMP [ 15 ], recombinase polymerase amplification (RPA) combined with lateral flow [ 16 17 18 ], PCR with a lateral flow strip [ 19 ], improved real-time PCR system with probe modification [ 20 ], CRISPR-Cas12a system coupled with PCR or LAMP [ 21 ], recombinase aided amplification combined with CRISPR/Cas12a [ 22 ], RPA-CRISPR-based nucleic acid detection method [ 23 ] and Crispr/cas12a technology combined with immunochromatographic strips [ 24 ]. The microfluidic-circular fluorescent probe-mediated isothermal nucleic acid amplification (CFPA) system has been newly developed for the detection of ASFV [ 25 ], and advanced nanopore sequencing has also been used for the diagnosis of ASFV [ 26 ].…”
Section: Introductionmentioning
confidence: 99%